Discharge equation of contracted rectangular falat-crested slit weirs / Rosley Jaafar and Ishak Abdul Azid - Jaafar, Rosley; Abdul Azid, Ishak (Universiti Teknologi MARA, Pulau Pinang, 2014)
This paper presents a study on water flow over a rectangular flat-crested slit weir where the discharge equation is obtained in terms of the dimensionless variable of H/P and H/t. This study was carried out on nine different weir heights with the weir width and weir crest thickness at 10 mm and 4 mm, respectively. The discharge coefficient is determined experimentally using the small discharges by varying weir heights. Regression analysis is conducted to establish the relationship of the discharge coefficient with both the H/P and the H/t taken as the variables. The linear relationship forms are obtained, which provide an easy means of estimating the discharge coefficient.